The Complete SEO Training Masterclass - Sarda, Shubham (Packt Publishing, 2019)
Mega search engine optimization course - learn keyword research, on-page and off-page SEO, link building, SEO audit, 20+ tools, negative SEO, WordPress SEO, and more! About This Video Optimize websites and improve user experience Generate more leads for your business by targeting keywords Rank websites and increase traffic on your website through a search engine In Detail Welcome to "Complete SEO Training Masterclass," one single course to start your SEO journey and go from beginner to advanced step-by-step. This course touches each important aspect of SEO, including all updates: Basic SEO vocabulary Important SEO industry terms Doing keyword research Implementing technical factors and page speed optimization Diving into website indexing and link building techniques Hands-on local SEO Protecting websites from negative SEO Learn to use 20+ different tools Performing SEO audit This course takes you to each topic in a connected way so you can relate to each topic and understand its importance. We will start with basic SEO vocabulary and end our course by learning about SEO audit, connecting with each topic in sequence one after another. You will also learn about common industry tools and learning how to use them will help you to run better and more efficient marketing campaigns. This course will help you to: Understand and master technical SEO factors Optimize websites to improve page speed and follow SEO guidelines Get indexed into search engines Utilize free tools available on the market Learn keyword research, Webmaster, local SEO, and a lot more Start building links from scratch Add free SSL certificates and CDN to our website to increase website speed and security Protect our website against negative SEO After completing this course, you will be ready to work on industry-level projects, and you will also be able to implement everything on your website itself!